2013
DOI: 10.1245/s10434-013-2995-5
|View full text |Cite
|
Sign up to set email alerts
|

The Financial Burden of Reexcising Incompletely Excised Soft Tissue Sarcomas: A Cost Analysis

Abstract: Reexcision of an incompletely excised sarcoma results in significantly higher professional charges when compared to a single, planned complete excision. Additionally, when the cost of the primary unplanned surgery is considered, the financial burden nearly doubles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 23 publications
2
26
0
1
Order By: Relevance
“…According to Alamanda et al, professional costs (i.e., charges billed by surgeons) significantly increased in re-resections compared with primary surgeries 18. Even after adjustment for influential parameters, such as tumour grade, site, size, and the fitness of patients before surgery, re-excisions were associated with a 33% increase in professional charges 18…”
Section: Discussionmentioning
confidence: 99%
“…According to Alamanda et al, professional costs (i.e., charges billed by surgeons) significantly increased in re-resections compared with primary surgeries 18. Even after adjustment for influential parameters, such as tumour grade, site, size, and the fitness of patients before surgery, re-excisions were associated with a 33% increase in professional charges 18…”
Section: Discussionmentioning
confidence: 99%
“…Factors that may influence charge accrual during initial treatment include: length of hospitalization, number of procedures, and type of procedures [16, 17, 18, 19]. For example, Petruzzelli et al .…”
Section: Discussionmentioning
confidence: 99%
“…These complications may precipitate additional interventions that can increase costs after initial treatment [16, 17, 18, 19]. Recent evidence has shown that utilizing staged reconstruction (SR) brachytherapy can minimize toxicity when compared to traditional IR [20].…”
Section: Purposementioning
confidence: 99%
“…Factors that may influence charge accrual during initial treatment include: length of hospitalization, number of procedures, and type of procedures [16,17,18,19]. For example, Petruzzelli et al noted a cost difference in regards to reconstructive modality [21].…”
Section: Discussionmentioning
confidence: 99%
“…These complications may precipitate additional interventions that can increase costs after initial treatment [16,17,18,19]. Recent evidence has shown that utilizing staged reconstruction (SR) brachytherapy can minimize toxicity when compared to traditional IR [20].…”
Section: Purposementioning
confidence: 99%